Population and Individual-Level Double Burden of Malnutrition Among Adolescents in Two Emerging Cities in Northern and Southern Nigeria: A Comparative Cross-Sectional Study - Oghenebrume Wariri; Kingsley Irelosen Akhimienho; Jacob Albin Korem Alhassan; Iliya Jalo; Iso Precious Oloyede; Eno Etim Nyong; Fidelia Bode-Thomas (Ubiquity Press, 2020)
Background: Over the past three decades, double burden of malnutrition (DBM), a situation where high levels of undernutrition (stunting, thinness, or micronutrient deficiency) coexist with overnutrition (overweight and obesity), continues to rise in sub-Saharan Africa. Compared to other countries in the region, the evidence on DBM is limited in Nigeria. Objective: This paper aimed to determine the comparative prevalence of population-level and individual-level DBM among adolescents in two emerging cities in northern and southern Nigeria. Methods: This was a comparative cross-sectional study among apparently healthy secondary school adolescents aged 10-18 years in Gombe (northern Nigeria) and Uyo (southern Nigeria) between January 2015 and June 2017. A multistage random sampling technique was implemented to recruit adolescents from 24 secondary schools in both cities. Measures of general obesity (body mass index) and stature (height-for-age) were classified and Z-scores generated using the WHO 'AnthroPlus' software, which is based on the WHO 2006 growth reference. Population-level DBM was defined as the occurrence of thinness and overweight/obesity within the population. Individual-level DBM was defined as the proportion of individuals who were concurrently stunted and had truncal obesity or stunted and were overweight/obese. Findings: Overall, at the population-level in both settings, 6.8% of adolescents had thinness, while 12.4% were overweight/obese signifying a high burden of population-level DBM. Comparatively, the population-level DBM was higher in Gombe compared to Uyo (thinness: 11.98% vs 5.3% and overweight/obesity: 16.08% vs 11.27% in Gombe vs Uyo respectively). Overall, at the individual level, 6.42% of stunted adolescents had coexisting truncal obesity, while 8.02% were stunted and had coexisting general overweight/obesity. Like the trend with population-level DBM, individual-level DBM was higher in Gombe (northern Nigeria) compared to Uyo (southern Nigeria). Conclusion: High levels of population-level and individual-level DBM exist in Gombe and Uyo. However, the level of DBM (under- and over-nutrition) is higher in Gombe located in northern Nigeria compared to Uyo in southern Nigeria.